TO ANALYZE THE DIETARY INTAKE AND DISEASE SEVERITY IN PSORIASIS PATIENTS - Chandak , Anshu (Journal of Biomedical and Pharmaceutical Research, 2020)
BACKGROUND: The most prevalent chronic inflammatory skin disease, psoriasis affects 0.5 to 4% of the population depending on the location. It is well known that psoriasis and metabolic syndrome increase each other’s risk when they coexist. It has been discovered that the autoimmune, inflammatory, and proliferative diseases of the epidermis have a polygenic genesis in psoriasis. One type of immune-mediated inflammatory illness is psoriasis. The enormous potential of gene polymorphism is outside the scope of this preview, and the critical role of epigenetics in nutritional biology is expounded upon. Nutrition has long been linked to skin integrity, health, and aging through a variety of skin biology-related processes and cofactors. Numerous nutrients have been found to provide skin photoprotection, and adequate dietary supplementation has been demonstrated to improve the appearance, maintain the integrity of the skin, and support skin health. It has been proposed that dietary patterns and behaviors have a significant impact on the development and clinical course of a number of common skin illnesses, including acne, psoriasis, atopic dermatitis, and hair loss. AIM: The aim of the present study was the dietary intake and severity of disease in patients with psoriasis. MATERIAL AND METHOD: In the Department of Dermatology, the current cross-sectional, observational, and analytical study was carried out. The study included 200 psoriasis patients, both male and female, who visited a dermatologist clinic. The values of the daily intake of dietary nutrients are the independent variables, also known as exposure variables. There are several macro and micronutrients among them. The clinical categories based on disease severity scores are the dependent variable. The study employed a structured questionnaire to gather data on the sociodemographic characteristics of the participants. Personal interviews were conducted with each patient to get information about their name, age, sex, place of residence, religion, and employment. RESULTS: In all, 200 psoriasis patients were included in the study. Based on three clinical classifications of patients with varying disease severity—Mild, Moderate, and Severe—a comparison of the observed parameters was conducted. 82.16% of the daily food intake amount that is advised was represented by the median of the observed daily calorie consumption. Overall, it was shown that as the disease severity increased, low-calorie intakes were more frequent and progressive. There was no discernible difference in the distributed frequency of instances around the median calorie consumption value throughout the illness severity categories. The recommended daily dietary intake of 40 grams of fiber per day was 93.26% of the total median consumption of dietary fiber. There was no discernible correlation between the various disease severity categories and the pattern of fiber consumption. CONCLUSION: The results obtained from this investigation are mostly in line with reports from laboratory, clinical, and epidemiological investigations. The synthesis of nutrient intake data is an attempt to define important perspectives for the necessary follow-up work toward the development of specific dietetic recommendations in psoriasis, in light of developments in pathogenic understanding. To develop specific dietary recommendations for psoriasis, focused studies on large-scale epidemiological and clinical perspectives predicted from the current study are necessary. Conducting scientific trials may never be possible due to the complex biology and subtle impacts of nutrition. KEYWORDS: Psoriasis, Micronutrients and Omega-3 Polyunsaturated Fatty Acids